PERANCANGAN MULTIMEDIA INTERAKTIF PROFIL DINAS PENANAMAN MODAL DAN PTSP KOTA BATAM SEBAGAI MEDIA INFORMASI: DESIGN OF INTERACTIVE MULTIMEDIA PROFILE OF BATAM CITY INVESTMENT AND PTSP AS INFORMATION MEDIA - Okta Veza; Regina Putri Risma (Engineering and Technology International Journal, 2020)
Advances in information technology have grown very rapidly so that it can help the performance of a company or government agency, one of which is interactive multimedia technology. The profiles of the Batam City Investment Service and PTSP agencies in hardcopy form are no longer feasible to be used as information media. With the use of Adobe Flash CS6 profiles can be run on computer or smartphone media and become a special attraction for recipients of information because of the animation. The design of interactive multimedia profiles of the Batam Investment Office and PTSP using the Multimedia Development Life Cycle (MDLC) method. The author hopes to produce Interactive Multimedia Design Profile of the Batam City Investment Office and PTSP to be more effective and innovative. So that it can make it easier for people in this digital era to find out related information at the Batam City Investment Office and PTSP.